2003
DOI: 10.1017/s0033291703008043
|View full text |Cite
|
Sign up to set email alerts
|

Corpus callosum in first-episode patients with schizophrenia – a magnetic resonance imaging study

Abstract: Our findings are in line with other in vivo morphometric studies on the CC in schizophrenia. The larger CC area in women may reflect general gender-related differences in CC size as described in healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 66 publications
(98 reference statements)
6
31
1
Order By: Relevance
“…This is consistent with earlier studies in prepubescent nonhuman primates (Sanchez et al, 1998; Coe et al, 2002), but not with a recently published report that found no differences in CC (Spinelli et al, 2009). Given the gender differences in the CC (Bachmann et al, 2003; Suganthy et al, 2003) and the gender-by-early stress effect on the CC (Coe et al, 2002; see Table 3), it is possible that Spinelli and collaborators (2009) were not able to detect a rearing effect on the CC as a result of using a mixed-gender cohort. In addition, they were not able to investigate the sex-by-rearing interaction due to a limited number of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with earlier studies in prepubescent nonhuman primates (Sanchez et al, 1998; Coe et al, 2002), but not with a recently published report that found no differences in CC (Spinelli et al, 2009). Given the gender differences in the CC (Bachmann et al, 2003; Suganthy et al, 2003) and the gender-by-early stress effect on the CC (Coe et al, 2002; see Table 3), it is possible that Spinelli and collaborators (2009) were not able to detect a rearing effect on the CC as a result of using a mixed-gender cohort. In addition, they were not able to investigate the sex-by-rearing interaction due to a limited number of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…[31,32] A great deal of literature has reported a reduction in CC area in schizophrenia patients and suggested an association between CC abnormalities and the occurrence of schizophrenia. [11,13,14] However, previous studies have found no differences in CC area regarding age, gender, course of illness or handedness in schizophrenia patients. [14,33,34] A recent MRI study of the CC using different methodologies suggested that age, sex and clinical status may affect the shape of the CC in schizophrenia patients.…”
Section: Discussionmentioning
confidence: 87%
“…[8] Rosenthal and Bigelow [9] first drew attention to an increased thickness of the CC in postmortem brains of schizophrenia patients. Later, in neuroimaging studies, CC size was found to be increased, [10] decreased [11] or unaltered [12] compared with healthy controls. In a meta-analysis of 28 magnetic resonance imaging (MRI) studies carried out by Arnone et al, [13] they found that schizophrenia patients seem to show a reduction in CC area.…”
Section: Articlementioning
confidence: 97%
“…Although not regarded as a prime candidate, there is growing evidence from diverse sources including neuroimaging that the CC is a locus of interest in schizophrenia; the first MRI study suggested alterations in size and shape in schizophrenia [28] . Subsequent analyses have found conflicting results, including global increases [28,29] , reductions [30,31] or no differences [32,33] compared to healthy individuals, although a meta-analysis of the first decade of CC studies in schizophrenia suggests this structure is smaller in patients [34] . Data in subjects experiencing their first episode of schizophrenia suggest that the CC may also be smaller than in healthy individuals [32,35,36] .…”
Section: Discussionmentioning
confidence: 99%